2008
DOI: 10.1016/j.trstmh.2008.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer in Bangladesh: community perceptions of cervical cancer and cervical cancer screening

Abstract: SummaryWe investigated the awareness of, and the attitude towards screening for, cervical cancer in Bangladesh. We performed a qualitative study using Focus Group Discussions (FGD). The framework approach to qualitative analysis was used.The study was performed in the catchment areas of Addin hospital, Jessore, Southern Bangladesh (peri-urban) and LAMB hospital, Parbatipur, North West Bangladesh (rural). 220 men, women and adolescents participated in 28 FGD.Awareness of cervical cancer was widespread. Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
5
24
2
Order By: Relevance
“…Perhaps it is less embarrassing to show private body parts to a female rather than a male health worker. Also, the likelihood of screening is also higher for women who did not believe that it was painful, which is consistent with other studies [17,19,23] . Perhaps they are more tolerant of the physical discomfort of the procedure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Perhaps it is less embarrassing to show private body parts to a female rather than a male health worker. Also, the likelihood of screening is also higher for women who did not believe that it was painful, which is consistent with other studies [17,19,23] . Perhaps they are more tolerant of the physical discomfort of the procedure.…”
Section: Discussionsupporting
confidence: 91%
“…This is confirmed by Singh et al's [14] study, which showed that a negative attitude of men towards screening or treatment of cervical cancer is considered a key factor contributing to poor uptake of services. Another study done in India revealed similar results [23]. In addition, women with college education had screened for cervical cancer more often compared to their counterparts.…”
Section: Discussionmentioning
confidence: 55%
“…This finding has been underlined by various other findings across local and regional boundaries [35][36][37][38][39]. However, there are studies that suggest that awareness and knowledge of cervical cancer and screening do not necessarily translate to uptake of cervical screening services [40].…”
Section: Discussionmentioning
confidence: 94%
“…Poor quality of service, cost, culture and lack of interest were not found to be barriers were not found to be barriers to cervical screening among the study groups. While the barriers to screening are supported by evidences from many other studies [12,17,35,36,38,[40][41][42][43], Cost [35,44] and quality of services [37,45] were indicated by other studies as important barriers to cervical screening uptake by women. These may not be important barriers for the study groups because they are only relevant for those who seek cervical screening which is not the case in our study.…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that availability of screening services influences awareness level about screening among the people. Another study in Bangladeshi rural community showed that limited availability of the services was related to less knowledge on prevention and screening tests (Ansink et al, 2008). Government has a strong heath infrastructure and it is already adopting cervical and breast cancer screening programme in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%